Exploring Characterization of the Main Character in Raya and the Last Dragon Movie - K.Divyani; Jayantini, I Gusti Agung Sri Rwa; Juniartha, I Wayan (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Abstract This article focuses specifically on the character analysis in Raya and the Last Dragon movie, especially the main character, namely Raya. This research is aimed to finding out main character’s characterization. The theory of characterization that proposed by Warren and Wellek (1962) was applied in this study. The research data were collected from Raya and the Last Dragon movie by watching the main character’s dialogue and action. Qualitative descriptive method was also used in conducting this research. There were 3 aspects of characterization that found in this movie namely, Raya was psychologically portrayed as a clever, determined, and cautions person. On the other hand, she was also socially described as Heart land’s princess, Chief Benja’s daughter, and dragon gem’s guardian. Lastly, she was physiologically illustrated to have black hair with braided and ponytail, big and black eyes, black eyebrows, brown skin, flat nose, and small lips when she was a child. However, when she was growing adult, she was depicted to have average height, thick black eyebrows, and long wavy hair, slim and slightly muscular. Keywords: Character, Characterization, Movie Abstrak Artikel ini berfokus secara khusus pada analisis karakter dalam film Raya and the Last Dragon, khususnya karakter Utama, yaitu Raya. Penelitian ini bertujuan untuk mengetahui penokohan karakter utama. Teori tentang penokohan yang diusulkan oleh Warren dan Wellek (1962) diaplikasikan pada penelitian ini. Data penelitian dikumpulkan dari film Raya and the Last Dragon dengan menonton dialog dan aksi karakter utama. Metode kualitatif deskriptif juga digunakan dalam melakukan penelitian ini. Adapun 3 aspek penokohan yang ditemukan dalam film ini diantaranya, Raya digambarkan secara psikologis sebagai seseorang yang cerdas, bertekad, dan berhati-hati. Di sisi lain, dia juga dideskripsikan secara social sebagai putri dari negeri Hati, anak kepala suku Benja, dan penjaga permata naga. Terakhir, dia diilustrasikan secara fisiologis memiliki rambut berwarna hitam yang dikepang dan diikat, mata yang besar dan berwarna hitam, alis tipis berwarna hitam, kulit coklat, hidung pesek, dan bibir tipis saat dia masih kecil. Namun, ketika beranjak dewasa, dia digambarkan memiliki tinggi rata-rata, alis tebal berwarna hitam, rambut panjang bergelombang, langsing, sedikit berotot. Kata kunci: Karakter, penokohan, Film